Epidemiological analysis of anaplasmosis in cattle from Khyber Pakhtunkhwa, Pakistan - Farhad Badshah; Kalim Ullah; Mustafa Kamal; Naseem Rafiq; Tahir Usman; Patricio R. De los Ríos-Escalante; Mourad Ben Said (Veterinary World, 2023)
Background and Aim: Anaplasmosis, a tick-borne disease affecting livestock caused by the bacteria Anaplasma, poses a global concern. This study aimed to estimate the prevalence, spatiotemporal variation, and associated risk factors of anaplasmosis in cattle from the Bannu and Lakki Marwat districts of Khyber Pakhtunkhwa, Pakistan.